The Rise of #IndonesiaTanpaJIL Youth Movement and the Fall of Liberal Islam on Cyberspace - Akmal Akmal (Universitas Darussalam Gontor, 2019)
AbstractSince its emergence, the discourse of Liberal Islam has invited much controversy. Several Muslim scholars consider it as nothing more than a continuation of the concepts previously delivered by Nurcholish Madjid or Harun Nasution. Initially discussed in academic forums and laid out in scientific papers, towards the end of the first decade in the 2000s, the discourse of liberal Islam was brought by its supporters to cyberspace, namely through the social media. This strategy has resulted in a rather dramatic change, prompting the emergence of the movement of young Muslims who call themselves #IndonesiaTanpaJIL (ITJ). Although most of its supporters are not scholars, the ITJ actions proved to be effective in discrediting the liberal Islam movement. Through observations in cyberspace, this research seeks to reveal the uniqueness of the ITJ movement and the measures it has taken to confront the liberal Islam. This work will also highlight several developments in the liberal Islam movement itself, resulting in the conclusion that liberal Islam is in fact can be seen as a discourse that has failed to develop in the cyberspace.Keywords: Cyberspace, Liberal Islam, IndonesiaTanpaJIL, Youth, Movement, Indonesia. AbstrakSejak kemunculannya, wacana Islam Liberal telah mengundang banyak kontroversi. Banyak sarjana Muslim menganggapnya hanya sebatas kelanjutan dari konsep-konsep yang sebelumnya telah diajukan oleh Nurcholish Madjid atau Harun Nasution. Jika awalnya dibahas dalam forum akademik dan dituangkan dalam karya-karya ilmiah, menjelang akhir dekade pertama tahun 2000-an, wacana Islam liberal dibawa oleh para pendukungnya ke dunia maya, yaitu melalui media sosial. Strategi ini telah menghasilkan perubahan yang agak dramatis, mendorong munculnya gerakan pemuda Muslim yang menyebut diri mereka #IndonesiaTanpaJIL (ITJ). Meskipun sebagian besar anggotanya bukanlah cendekiawan, aksi-aksi ITJ terbukti efektif dalam mendiskreditkan gerakan Islam liberal. Melalui pengamatan di dunia maya, penelitian ini berupaya mengungkapkan keunikan pergerakan ITJ dan langkah-langkah yang diambilnya untuk menghadapi Islam liberal. Karya ini juga akan berupaya menyoroti sejumlah perkembangan dalam pergerakan Islam liberal itu sendiri, sehingga menghasilkan kesimpulan bahwa Islam liberal pada kenyataannya dapat dipandang sebagai sebuah wacana yang telah gagal berkembang di dunia maya.Kata Kunci: Cyberspace, Islam Liberal, IndonesiaTanpaJIL, Pemuda, Pergerakan, Indonesia.